Ultrasonic monitoring for the evaluation of conditioning by training session for athletes - Hossain, M.; Grill, W. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Non-intrusive ultrasonic detection scheme has been implemented to monitor and quantify the loading effect of training sessions on athletes. The detection is obtained along a line between two acoustic transducers with similar size and shape as stick-on electrodes. All the data is derived from the transmission time-of-flight of the ultrasonic chirp signal passing through the muscle and the ultrasonic force sensor. Muscle dynamics and force generated due to maximum isometric contraction was synchronously detected with the aid of an arbitrary function generator and a two channels transient recorder. At least 16 performance deciding parameters of athletes are quantified. The achieved spatial and temporal resolutions are ± 0.01 mm and 0.01 ms respectively. Detected movement reaction time could be used as a potential indicator to identify false-start in athletics, swimming and other necessary fields.